1994
DOI: 10.3109/02652049409040443
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-release dosage form of nitrofurantoin. Part 1. Preparation of microcapsules and in vitro release kinetics

Abstract: A new sustained-release dosage form of nitrofurantoin as microcapsules was prepared by carboxymethylcellulose-aluminium sulphate simple coacervation technique. In vitro release studies for microcapsules and their formulated hard gelatin capsule and tablet forms were performed. Release rates were studied as functions of core: wall ratios and the particle sizes of the microcapsules. Dissolution tests of microcapsules and their dosage forms were studied in simulated gastric and intestinal media without enzyme usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Microcapsules of ketoconazole were prepared by means of a phase separation technique, which is a simple coacervation method (Ertan et al 1994). Sodium carboxymethylcellulose is added into boiling water and mixed thoroughly until it cools.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…Microcapsules of ketoconazole were prepared by means of a phase separation technique, which is a simple coacervation method (Ertan et al 1994). Sodium carboxymethylcellulose is added into boiling water and mixed thoroughly until it cools.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…Microparticles prepared with the combination of NTF}CAP}CAB in the ratio of 1.0: 0.4 :1.6 showed the greatest delay in drug release in SGM. Earlier work by Ertan et al (1994) showed that a sustained-release dosage form of NTF as microcapsules could be prepared by a carboxymethylcel-lulose± aluminium sulfate coacervation technique. With their polymer mixture, approximately 60 % of the drug was released in SGM in 5 h compared with the 20 % released by our formulation of NTF}CAP}CAB (1.0 : 0.4 : 1.6).…”
Section: In-vitro Dissolution Studiesmentioning
confidence: 99%
“…However, the gastric side-eOE ects could not be completely overcome by using macrocrystals in the formulation. Therefore, many attempts have been made to reduce the gastric side-eOE ects by controlling the drug release in the stomach, for example by using sustained release tablets, hard gelatin capsules and microcapsules (Baichwal & Shetty 1982 ;Eldem & Capan 1983 ;Ertan et al 1994). However, when these dosage forms are used to treat childhood urinary tract infections, which occur in 2 % of boys and 8 % of girls by 10 years of age (Roy 1999), the di culty of swallowing tablets or capsules could result in non-compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have investigated the reduction of these side effects of NF using macrocrystalline [12] and the sustained release of oral dosage forms e.g. tablets [13], capsules, microcapsules [14] and microparticles [15].…”
Section: Introductionmentioning
confidence: 99%